MINIMIZING ADVERSE IMPACT OF DROUGHT: ROLE OF GOVERNMENT AND FINANCIAL INSTITUTIONS - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
For India, droughts and floods in one or the other parts of the country are regular features every year. History records 24 major drought years during 121 years from 1891 to 2012 that include 15 droughts since country’s independence. The year 2015-16 [July-June] was predicted to be a drought year since the India Meteorological Department had projected 88% of normal monsoon rainfall. This is expected to produce 253.16 million tons of food output much less than 265.04 million tons in 2013-14.According to the latest press reports in April-May 2016 already quarter of the country, 313 districts, 1,58,205 villages and 4,44,281 dwellings in 12 States have been hit hard drying up traditional source of drinking water too as on end-April 2016.Coping with drought requires meticulous planning to conserve rainwater and economize on its use. Water-guzzling crops like sugarcane, paddy and even hybrid cotton need to be discouraged in water-stressed area. Around 15.38% of 650 billion cubic meters [BCM] water available for irrigation is used by sugarcane (the crop uses water from reservoirs as well as groundwater), which is planted on no more than 2.5% of India’s farmland. Sugarcane uses a disproportionate amount of water. This paper focuses the need to make the role of the Government and rural financial institutions effective to minimize impact of drought and suggests the strategic action plan to harness the available irrigation potential including recycling the use of wastewater and improving water use efficiency through micro-irrigations schemes with the support of institutional credit.